THE AIR POLLUTION AND SOUND MANAGEMENT OF AUTOMOTIVE MECHANICAL ENGINEERING LABORATORY - - Murdani (Jurnal Penelitian Saintek, 2016)
This study was aimed at: (1) determining the reduction of noice pollution after using extra mufﬂ er, (2) calculating the reduction of air pollution after using heater reactor. The both of the research is conducted in automotive-mechanical engineering laboratory. This study was used experimental method. The instruments used in this study were: (1) gas analyzer and smoke tester, (2) digital thermometer, and (3) sound level meter. The results show that the use of extra mufﬂ er in the automotive-mechanical engineering laboratory of State University of Semarang is able to decrease of sound power of 9.46 percent. The mean of sound level before using extra mufﬂ er was 69.58dB, while the magnitude of the mean level after using extra mufﬂ er is 63 dB. Electrical heater as a thermal reactor is able to reduct CO level of 1.888 percent and HC level of 262 percent in the exhaust gas. The measurement of CO level of exhaust gas emission before using the reactor was 1.888 percent and HC level of 262 ppm, while CO level and HC level after using the reactor is 1.521 percent and 237 ppm.